Polypharmacy among Older Individuals with COPD: Trends between 2000 and 2015 in Quebec, Canada. (4th July 2019) - Sirois, Caroline; Ouali, Amina; Simard, Marc
Abstract: The treatment of chronic obstructive pulmonary disease (COPD) and concomitant diseases requires several medications. Yet there is little data on how the pharmacological burden progressed over time among older individuals with COPD. We aimed to: 1) describe the proportion of older adults with COPD in Quebec, Canada, that were exposed to polypharmacy (≥10, ≥15 or ≥20 medications/year) between 2000 and 2015; 2) calculate the proportion of individuals receiving specific prescriptions for COPD during this period. We conducted a population-based cohort study with the Quebec Integrated Chronic Disease Surveillance System. Individuals aged ≥66 years with COPD and covered by the universal public drug plan were included. We calculated the total number of drugs used at least once by each individual during each of the studied years, and used age-standardized proportions to compare proportions of users between the years. The average number of drugs used increased from 12.0 in 2000 to 14.8 in 2015. The proportion of individuals exposed to polypharmacy increased (≥10 drugs: 62.0% to 74.6%;≥15 drugs: 31.2% to 45.4%; ≥20 drugs: 12.3% to 22.4%). The proportion of individuals receiving long-acting bronchodilators increased from 18.7% in 2000 to 69.6% in 2015. The use of short-acting bronchodilators decreased from 81.5% to 67.9%, and that of inhaled corticosteroids from 60.6% to 26.0%. The proportion of users of methylxanthines decreased from 15.0% to 1.9%. Older individuals with COPD are increasingly exposed to polypharmacy. Identifying which polypharmacy is beneficial is a priority.